Prior knowledge in teaching Biology about Annelida Phylum and the Vermicomposting (Research, Society and Development, 2025)
Vermicomposting is a natural and biological process that uses earthworms, representatives of the Annelida Phylum, as labor in the recycling of organic compounds, resulting in the production of humus. In addition to being a natural process of soil fertilization, reducing the accumulation of domestic organic waste wasted in the environment, it can be used as a methodological resource in teaching the Annelida Phylum, especially the Oligochaeta Class. In this sense, this work aims to develop a pre-analysis to support the development of didactic-pedagogical sequences of investigative teaching, offering new approaches that contribute to the learning process of the Annelida Phylum. The methodology applied to this research was quantitative and qualitative, with a structured questionnaire as a research instrument to survey the participating students regarding their prior knowledge about the representatives of the Annelida Phylum, their ecological importance, Vermicomposting and reuse of Domestic Organic Waste (DOW). The application of a survey questionnaire revealed that the students had significant gaps in their knowledge about the Annelida Phylum, its ecological relevance and vermicomposting. More than half of the participants demonstrated lack of knowledge of the term “annelids” and its representatives, even mentioning organisms from other phyla. Although the majority associated earthworms with the annelid group, a superficial understanding of their ecological importance was evident. In addition, the research indicated that the students had little knowledge about vermicomposting and the correct disposal of household organic waste, which, in most cases, was discarded in landfills together with regular garbage.